The relation of maxillary root apices and the maxillary sinus floor among patients with different skeletal patterns in Iraqi samples - Karrar H Al sultany; Iman I Al sheakli (College of Dentistry/ University of Baghdad, 2018)
Background: Understanding the morphological characteristics between the floor of the maxillary sinus and the tips of the maxillary posterior roots is crucial in orthodontics involving diagnosis and treatment planning. The aim of this study was to evaluate the distances from the maxillary posterior root apices to the inferior wall of the maxillary sinus, thickness and density of maxillary sinus floor using cone-beam computed tomography images and the relationships between roots and maxillary sinus according to gonial angle and skeletal pattern. Materials and methods: Three-dimensional images of each root were checked, and the distances were measured along the true vertical axis from the apex of the root to the sinus floor, and the thickness and density of maxillary sinus floor in 60 patients (30 males, 30 female) aged 18 to 25 years. Evaluation of the differences between groups which classified to gonial angle and skeletal pattern which were done according to the comparsion between the mean statistic tests. Results: results showed that the density of floor of maxillary sinus at the first molar roots region in class III were significantly lower than class I and II, also the distance between the floor of maxillary sinus and both distobuccal and palatal roots of first molar were significantly lower in class I than other classes, while the thickness of maxillary sinus floor at the distobuccal root of first molar were significantly higher in class III than other classes. In gonial angle difference, the maxillary sinus floor density and distance to the maxillary posterior roots had no significant difference in all groups, while the thickness of maxillary sinus floor at distobuccal and palatal of second molar roots region were significantly higher in large gonial angle than small and normal angles. Conclusion: subjects with class I skeletal pattern have small distance between the maxillary sinus floor and the maxillary posterior roots due to the pneumatisation of maxillary sinus causing more difficult and time consuming orthodontic treatment.